Financial Interdependence of International Stock Markets: A Literature Review - Mitra, Amarnath; Bhattacharjee, Kaushik (Indian Journal of Finance, 2015)
In financial literature, interdependence of capital markets is synonymous with the measure of co-movement between them. Hence, the necessity to understand the genesis of interdependence of stock markets arises from its consequences on monetary and trade policies, resource allocation, capital requirements, and risk hedging. The co-movement of stock indices has been the subject of study since 1970s, and researchers have studied the time-varying correlations and impact of new information on stock returns. This study surveyed the existing literature on linkages between international stock markets. We provided an up-to-date coverage of studies on importance and drivers of stock market linkages. The paper also provided a review of contemporary methodologies to evaluate the level of integration between international stock markets. Our study provided an appendage to the existing literature on how the area of research on interdependence of stock markets has evolved with a focus on its cause and effect on the level of market integration and also highlighted the scope for further research in this area.